Decentering Islamic Authority in The Digital Sphere: Gus Baha’s Al-Hikam and The Reconfiguration of Vernacular Sufism in Indonesia - Muhammad Sulthon; Mahmud Yunus Musthofa; Mishbah Khoiruddin Zuhri (Tribakti: Jurnal Pemikiran Keislaman, 2025)
This study aims to address the lack of scholarly attention to the dominance of Western colonial knowledge and the strategies for restoring local Islamic epistemic authenticity in Indonesia’s digital public sphere. Specifically, it examines the digital preaching strategies of Gus Baha in his online Al-Hikam studies, focusing on how local religious elites rearticulate vernacular Islamic authority through digital media while maintaining harmony with their followers. The research employs a qualitative approach using digital ethnography and interpretive content analysis of four YouTube channels that regularly disseminate Gus Baha’s Al-Hikam lectures. The findings reveal three central strategies in Gus Baha’s digital da‘wa: re-centering pesantren authority through online kitab kuning recitations, emphasizing sanad (chain of knowledge transmission) as a marker of epistemic authenticity, and adapting Sufi teachings into accessible audiovisual formats without losing their intellectual and spiritual depth. These strategies demonstrate how pesantren-based scholarship, classical Sufi teachings, and Javanese cultural values are revitalized within the contemporary digital ecosystem, providing an alternative to dominant globalized and textualist Islamic discourses. Theoretically, this study contributes to the discourse on digital religion and Islamic authority by showing how vernacular Sufism, mediated through online platforms, enables local scholars to resist Western epistemic dominance. It affirms the continuity of traditional Islamic scholarship while opening possibilities for plural epistemologies in understanding Islam in the digital age.